(untitled) (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2020)
Professional burnout is a well-documented issue in professional psychology and has been associated with multiple negative personal, professional, and institutional consequences. Interestingly, burnout in the context of psychologists-in-training has received very little attention. This article defines burnout in the context of professional psychology, outlines the factors leading to burnout, discusses burnout in the context of psychologists-in-training, and examines how clinical supervisors can play a preventative and/or remedial role in supervisee burnout. The article concludes by highlighting the need to integrate education and wellness plans into supervisory relationships and settings.